Clinical and radiographic analysis of traumatized primary teeth and permanent successors: Longitudinal study - Pugliesi, Daniela Maria Carvalho; Araujo, Lisa Danielly C.; Junior, Valdeci Elias S.; Cunha, Robson F. [UNESP] (Wolters Kluwer, 2020)
Background: Dental trauma can determine the occurrence of sequelae in the deciduous tooth and due to the anatomical proximity to the germ of the successor permanent tooth, it frequently causes changes to the developing teeth. Aims: The objective of this study was to analyze clinically and radiographically traumatized primary teeth and permanent successors in children aged 0–8 years. Materials and Methods: Initially, a sample selection of medical records was made, designating the patients who fit the requirements; 247 patients were analyzed, totaling 379 traumatized primary teeth and 162 successive permanent teeth. Statistical Analysis: The results were developed using the Proportion Test and the Chi-square test at the 5% significance level. Results: Injuries to hard tissue prevailed (57%), with emphasis on coronary enamel fracture (49.1%). After clinical and radiographic examinations, 78% of traumatized primary teeth maintained pulpal vitality. At the clinical evaluation, the frequency of the developmental disorders observed in permanent successors was 10.5%, with enamel hypocalcification being the most common sequela. 17.3% of the clinical changes in the successor permanent teeth were caused by trauma to the supporting tissue, with the intrusive dislocation being responsible for the largest number of damages (37.5%). Conclusion: Based on the results found, it was concluded that the trauma occurring in the primary dentition were recorded and monitored more precisely and about the evaluated successive permanent teeth, except for the prevalence of sequelae found, the other factors are in agreement with the findings in the literature.
Keywords: Dental enamel; Dental trauma; Permanent dentition; Primary dentition